Relationships among Walleye Population Characteristics and Genetic Diversity in Northern Wisconsin Lakes. Issue 3 (30th April 2014) - Waterhouse, Matthew D.; Sloss, Brian L.; Isermann, Daniel A.
Abstract: The maintenance of genetic integrity is an important goal of fisheries management, yet little is known regarding the effects of management actions (e.g., stocking, harvest regulations) on the genetic diversity of many important fish species. Furthermore, relationships between population characteristics and genetic diversity remain poorly understood. We examined relationships among population demographics (abundance, recruitment, sex ratio, and mean age of the breeding population), stocking intensity, and genetic characteristics (heterozygosity, effective number of alleles, allelic richness, Wright's inbreeding coefficient, effective population size [ Ne ], mean d 2 [a measure of inbreeding], mean relatedness, and pairwise population ΦST estimates) for 15 populations of Walleye Sander vitreus in northern Wisconsin. We also tested for potential demographic and genetic influences on Walleye body condition and early growth. Combinations of demographic variables explained 47.1–79.8% of the variation in genetic diversity. Skewed sex ratios contributed to a reduction in Ne and subsequent increases in genetic drift and relatedness among individuals within populations; these factors were correlated to reductions in allelic richness and early growth rate. Levels of inbreeding were negatively related to both age‐0 abundance and mean age, suggesting Ne was influenced by recruitment and generational overlap. A negative relationship between the effective number of alleles and body condition suggests stocking affected underlying genetic diversity of recipient populations and the overall productivity of the population. These relationships may result from poor performance of stocked fish, outbreeding depression, or density‐dependent factors. An isolation‐by‐distance pattern of genetic diversity was apparent in nonstocked populations, but was disrupted in stocked populations, suggesting that stocking affected genetic structure. Overall, demographic factors were related to genetic diversity and stocking appeared to alter allelic frequencies and the genetic structure of Walleye populations in Wisconsin, possibly resulting in disruption of local adaptation.